ASYMPTOTIC GIANT BRANCH VARIABLES - Whitelock, P. A. (Одеські астрономічні публікації, 2017)
Asymptotic Giant Branch variable are the brightest and most distinctive individual stars to be found in the resolved, old and inter mediate age, stellar populations of galaxies in the Local Group and beyond. The characteristics of these stars are reviewed here with particular emphasis on the luminous AGB stars in the LMC. Moat large amplitude variables, both carbon- and oxygen-rich, fall close to a linear extrapolation of the period luminosity relation determined for shorter period Miras. The few such stars which are more luminous than predicted appear to be experiencing extra energy production via hot bottom burning.